EISCAT/CRRES observations: Nightside ionospheric ion outflow and oxygen-rich substorm injections - Gazey, NGJ; Lockwood, M; Grande, M; Perry, CH; Smith, PN; Coles, S; Aylward, AD; Bunting, RJ; Opgenoorth, H; Wilken, B (SPRINGER VERLAG, 1996)
We present combined observations made near midnight by the EISCAT radar, all-sky cameras and the combined released and radiation efects satellite (CRRES) shortly before and during a substorm. In particular, we study a discrete, equatorward-drifting auroral are, seen several degrees poleward of the onset region. The are passes through the field-aligned beam of the EISCAT radar and is seen to be associated with a considerable upflow of ionospheric plasma. During the substorm, the CRRES satellite observed two major injections, 17 min apart, the second of which was dominated by O+ ions. We show that the observed are was in a suitable location in both latitude and MLT to have fed O+ ions into the second injection and that the upward flux of ions associated with it was sufficient to explain the observed injection. We interpret these data as showing that arcs in the nightside plasma-sheet boundary layer could be the source of O+ ions energised by a dipolarisation of the mid- and near-Earth tail, as opposed to ions ejected from the dayside ionosphere in the cleft ion fountain.